Analyser les impacts des circuits courts alimentaires : une étude en Nord-Pas-de-Calais - Amélie Gonçalves; Thomas Zeroual (Revue de la régulation, 2016)
Short food supply chains seem to be a virtuous alternative to classical food chains notably to ensure a sustainable food supply of cities. However, there are some doubts as to whether they deserve this reputation. Numerous researches have indeed shown different economic, social and environmental impacts according to the short supply chain. However, these effects and the potential role of these chains in a more sustainable agriculture are not straightforward. The plurality of possible definitions of these chains is an explaining factor of this phenomenon, leading to a diversity of perimeters and modes of assessment. This article’s goal is to provide a different definition of these short chains based on the framework of the Econonomics of Convention, especially the one of the “worlds of production”. Based on this new definition, we then provide a comparative assessment of different types of short chains. To achieve this, we focus on a specific type of impacts: the ones of logistics. The demonstration is based on the study of short chains with one intermediate in the French region of Nord-Pas-de-Calais. The research shows how and in what measures the specific performance requirements of a world of production and its related short food supply chains – permanent supply, strong price competition – explain the lack of sustainability regarding the logistics of some short chains. As a consequence, the reduction of some of these specific requirements appears as a mean of increasing the sustainability of these chain’s logistics.